Impact assessment caused by bradyseism phenomena in the Campi Flegrei area - Perelli, Francesca Linda; Di Maio, Luigia Sara; De Gregorio, Daniela; Magliulo, Gennaro; De Martino, Prospero; Zuccaro, Giulio (Frontiers in Built Environment, 2023)
Campi Flegrei (Italy) is among the areas with the greatest volcanic explosive risk in the world, due to the dangerousness of the expected hazards, the high exposed value (about 500,000 people will be evacuated during the ‘alarm phase’) and the vulnerability of the urban settlements under effect of the volcanic phenomena. The events expected in case of Campi Flegrei eruption are: precursor earthquakes due to the ascent of magma of shallow depth (<5km) and magnitude not exceeding 4.2; fallout of ash with thickness even greater than 1m; pyroclastic flows that can affect a quite considerable area of the municipality, depending on the position of the eruptive vent. Added to this a peculiar phenomenon, called ‘bradyseism’, characterized by slow movements of the soil linked to magmatic-hydrothermal processes, is already in progress. Since at least Greek-Roman time, many bradyseism episodes occurred in Campi Flegrei area, but only once, in 1538 CE, after a ground uplift of 16 m, an eruption was recorded and a new volcano came out (Monte Nuovo). The last two dramatic bradyseism phases occurred in 1969–1972 and 1982–1984, where Pozzuoli town has been affected by a rapid ground inflation which brought to an overall higher level of about 3.5m and caused numerous earthquakes (M≤4.2), with severe damage to buildings. . The need to better understand Campi Flegrei volcanic activity is fundamental to protect the population from hazards linked to explosive volcanic eruptions and to understand the role of seismicity as a possible precursor of a potential eruption. In this perspective, as part of the activities of PLINIVS Study Centre (Centre of Competence of Italian Civil Protection Department for volcanic risk), the authors developed a procedure, implemented in a web application, that relates the monitoring of the ground deformation with the behaviour of buildings, to evaluate near real time the level of progressive damage to the ordinary Phlegraean buildings due to bradyseism. This article describes the models adopted for the three impact/risk factors (hazard, exposure and vulnerability) used to estimate the damage of the buildings.